Effective short term Siddha treatment of filiform warts using Rasaganthi Mezhugu - Sundaramahalingam, Lalithakumari; Gnanaraj Johnson, Christian (International Journal of Research in Medical Sciences, 2025)
Filiform wart is a non-cancerous, contagious and outwardly growing skin lesion caused by the Human Papillomavirus (HPV). It is characterized by slender, finger-like projections from the squamous epithelium, a condition known as papillomatosis. These lesions are most commonly observed on the neck, eyelids, and fingers. If left untreated, filiform warts may spread to other parts of the body. The virus prompts the skin to produce an excess of keratin leading to the formation of long, narrow growths. Conventional treatments for warts include immunotherapy, laser therapy, phytotherapy, and topical medications. However, these methods are often time-consuming, expensive and may require multiple or repeated sessions due to recurrence. Warts may reappear if HPV remains in the surrounding skin. In the Siddha system of medicine, warts are referred to as Marul, classified under Thol Noikal (skin disorders). One effective remedy recommended is Rasagandhi Mezhugu (RGM), traditionally used for treating various skin ailments. A recent case study documented the successful treatment of a 36-year-old male patient with 19 filiform warts on his neck. He was administered 500 mg of RGM internally for 15 consecutive days following the intake of curd rice. No external applications were used. Within two weeks, the hyperkeratinized projections began to shrink, detach and completely disappear. The treatment reported no adverse effects and no recurrence of the warts till date. This case highlights the therapeutic potential of Rasagandhi Mezhugu in managing filiform warts caused by HPV. The outcome demonstrates its efficacy and safety as a natural alternative for wart treatment.